Sensory sensitivity after acquired brain injury: A systematic review. Issue 1 (30th June 2022) - Thielen, Hella; Tuts, Nora; Welkenhuyzen, Lies; Huenges Wajer, Irene M. C.; Lafosse, Christophe; Gillebert, Céline R.
Abstract: Patients with acquired brain injury frequently report experiencing sensory stimuli as abnormally under‐ (sensory hyposensitivity) or overwhelming (sensory hypersensitivity). Although they can negatively impact daily functioning, these symptoms are poorly understood. To provide an overview of the current evidence on atypical sensory sensitivity after acquired brain injury, we conducted a systematic literature review. The primary aim of the review was to investigate the behavioural and neural mechanisms that are associated with self‐reported sensory sensitivity. Studies were included when they studied sensory sensitivity in acquired brain injury populations, and excluded when they were not written in English, consisted of non‐empirical research, did not study human subjects, studied pain, related sensory sensitivity to peripheral injury or studied patients with a neurodegenerative disorder, meningitis, encephalitis or a brain tumour. The Web of Science, PubMed and Scopus databases were searched for appropriate studies. A qualitative synthesis of the results of the 81 studies that were included suggests that abnormal sensory thresholds and a reduced information processing speed are candidate behavioural mechanisms of atypical subjective sensory sensitivity after acquired brain injury. Furthermore, there was evidence for an association between subjective sensory sensitivity and structural grey or white matter abnormalities, and to functional abnormalities in sensory cortices. However, further research is needed to explore the causation of atypical sensory sensitivity. In addition, there is a need for the development of adequate diagnostic tools. This can significantly advance the quantity and quality of research on the prevalence, aetiology, prognosis and treatment of these symptoms.